SOIL CHARACTERISTICS, MICROBIAL BIOMASS CARBON AND NITROGEN UNDER DIFFERENT LAND USE PATTERNS IN RED SOILS OF VIKARABAD DISTRICT - TRIVENI. S and BHANU REKHA. K, APOORVA. M.R, PADMAJA. G, S.H.K. SHARMA (The Journal of Research, PJTSAU, 2023)
The microbial biomass of soil is being increasingly recognized as a sensitive indicator of soil quality. Its knowledge is fundamental for sustainable environment management. This study is aimed to determine the impact of different land use patterns i.e., forest land,100% cropping intensity (redgram-fallow), 200% cropping intensity (rice-rice) and fallow land on soil microbial biomass carbon and nitrogen. A survey was conducted for two successive years (2019-20 and 2020-21) in red soils of Vikarabad district of Telangana state covering eight mandals and soil samples were collected from four different land use patterns at two depths (0-15 and 15-30 cm). Soil characteristics like bulk density, pH, EC, organic carbon, total nitrogen varied significantly with land use patterns and soil depth and were significantly higher in forest soils compared to other land use patterns. The mean microbial biomass carbon found to be 242.8 mg kg-1, 128.1 mg kg-1, 119.0 mg kg-1, 69.0 mg kg-1 and the mean soil microbial nitrogen was found to be 35.6 mg kg-1, 21.9 mg kg-1, 17.7 mg kg-1 and 11.0 mg kg-1 respectively for forest, 100% cropping intensity, 200% cropping intensity and fallow land. There was significant positive correlation of microbial biomass carbon with per cent clay (0.998**), soil organic carbon (0.992**), total nitrogen (0.984**) and microbial biomass nitrogen (0.997**). The results confirm that alterations in soil physical and chemical properties due to deforestation and intense anthropogenic activity at agriculture lands may cause disturbances and ultimately affect the soil microbial biomass.